Physical properties of newly developed resin modified glass ionomer cement with synthesised coumarin derivatives - Fatimah Suhaily Abdul Rahman,; Dasmawati Mohamad,; Habsah Hasan,; Hasnah Osman, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The aim of this study was to determine the effects of two types of coumarin derivatives, namely, 3-acetylcoumarin (AC) and coumarin thiosemicarbazone (CT) on surface characteristics such as the roughness, hardness, and morphology of resin-modified glass-ionomer cement (RMGIC). The release of coumarin from the fabricated RMGIC was also investigated. AC and CT at 1.0% (w/w) concentration were added into 0.3 g of RMGIC powder and mixed with 0.1 g of polyacrylic acid. The fabricated RMGIC-AC and RMGIC-CT were evaluated for surface characteristics such as roughness, hardness and topography. The coumarin release of AC and CT from RMGIC was also determined. The RMGIC-CT demonstrated a decreased roughness value among the materials. The surface roughness exhibited by the RMGIC was statistically higher (p < 0.05) than that of fabricated materials. The RMGIC-AC was observed to have the highest hardness value compared to the RMGIC-CT and RMGIC, and this value was significantly higher (p < 0.05). The surface morphologies of the RMGIC-AC and RMGIC-CT showed a number of pores and irregular surfaces. Meanwhile, the surface roughness value of the RMGIC was statistically higher (p < 0.05) than both RMGIC-AC and RMGIC-CT. In conclusion, the large-sized AC particles significantly increased the surface hardness of the fabricated RMGIC. Conversely, the particle size of both coumarins were not influenced the surface roughness value and the coumarin release profile of fabricated RMGICs.